BETWEEN PSYCHOSOCIAL CARE AND HOBBY: THERAPEUTIC WORKSHOPS IN MENTAL HEALTH FIELD - Monteiro Lima, Ana Flavia; Peres, Rodrigo Sanches [UNESP] (Univ Estado Rio Janeiro, 2018)
In Brazilian mental health services, namely in the Psychosocial Care Centers (CAPSs), several intervention tools have been used. The therapeutic workshops stand out as one of the main ones. The present study aimed to establish, through a literature review, an overview of the scientific production carried out in the format of article about the therapeutic workshops in the mental health field in Brazil. The following databases were consulted: Periodicos Eletronicos de Psicologia (PEPsic), Base de Dados de Enfermagem (BDEnf) and Scientific Electronic Library Online-Brasil (SciELO-Brasil). The localized references were sorted to enable the discarding of possible duplications and then selected according to the theme. The corpus of analysis consisted of 11 references. It was found that the objectives of such references were relatively diverse, but most of them did not provide information on the frame of the therapeutic workshops they addressed. In any case, the references pointed out that such intervention tools, specially from the artistic expression and the work, fomented the interaction between the users, as well as the development of different abilities and, consequently, they provided subsidies for the psychosocial care. On the other hand, in some references, there were indications that the therapeutic workshops researched, at least in part, appeared as mere tasks to be performed mechanically by the users, because were conceived or ended up functioning as a kind of hobby. The present study, therefore, can be considered potentially useful for researchers and health professionals interested in the subject.
Keywords: Mental health; Therapeutic workshops; Psychiatric Reform